ANALISIS PENDAPATAN USAHA PADI (Oryza sativa L) SAWAH PASANG SURUT DI KELURAHAN TAMBAK KARYA KECAMATAN KURAU KABUPATEN TANAH LAUT PROVINSI KAL SEL - Wasdiyanta Wasdiyanta; Zuraida Zuraida (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
This study aims to determine the technical aspects of farming and economically the costs, and income of tidal lowland rice farming. Sampling was done by simple random sampling method of 30 farmers. From the observations, it is known that the production obtained from 30 respondent farmers with an average land area of 1.6 ha is 427.36 blek / farmer / ha or 4,701,033 kg / farmer / ha (470 ton / ha / farmer). Total revenue is Rp. 628,150,000.00 and an explicit fee of Rp. 207,080,999.84 thus the income of the respondent farmers was IDR 421,069,000.16 or an average of IDR 14,035,633.34 / farmer.